Predictive Significance of Vascular Endothelial Growth Factor receptor VEGF-2 in triple-negative breast cancer patients - N. N. Babyshkina; M. V. Zavyalova; O. D. Bragina; T. A. Dronova; E. M. Slonimskaya; N. V. Cherdyntseva (Сибирский онкологический журнал, 2016)
The identification of informative biomarkers that are able to predict prognosis and treatment response may be particularly important in triple negative breast cancer.The aim of the study was to investigate the relationship between vascular endothelial growth factor receptor VEGFR-2 expression and KDR gene polymorphisms with the efficacy of neoadjuvant chemotherapy (NAC) in patients with triple negative breast cancer.Methods. The study included 70 patients with triple negative operable breast cancer (T1–3N0–3M0), who had received 2–4 cycles of FAC and CAX regimens. The pathologic complete response (pCR) to treatment was determined by RECIST. VEGFR-2 expression level was evaluated using immunohistochemistry. Genotypes for KDR (rs2071559, rs2305948) were detected by a Real-time PCR.Results. The pCR rate was significantly associated with young age at diagnosis (≤50 years) (p=0.0044), a high level of Ki67 expression (≥20) (p=0.0322) and with CAX regimen (p=0.0246). Additionally, all patients with pCR had the lack of VEGFR-2 expression in tumor tissue after surgery (p=0.0000). The presence of the VEGFR-2 expression (negative or positive) in tumor tissue before NAC was associated with KDR rs2071559 (r=−0.297; p=0.0273). A significant correlation between the KDR rs2071559 and VEGFR-2 expression level (less than 70, 70% or more) in the tumor tissue before NAC was found (r=−0.314; p=0.0297). Multivariate logistic regression analysis showed that the young age of the patients (≤50 years), the lack of VEGFR-2 expression after surgery and CAX regimen were significant predictors of NAC.Conclusion. The VEGFR-2 expression level in tumor tissue and KDR gene polymorphism can be considered as new additional molecular predictive markers of pathologic complete response to NAC in triple negative breast cancer patients.